Evaluating best educational practices, student satisfaction, and self-confidence in simulation: A descriptive study. (January 2018) - Zapko, Karen A.; Ferranto, Mary Lou Gemma; Blasiman, Rachael; Shelestak, Debra
Abstract: Background: The National League for Nursing (NLN) has endorsed simulation as a necessary teaching approach to prepare students for the demanding role of professional nursing. Questions arise about the suitability of simulation experiences to educate students. Empirical support for the effect of simulation on patient outcomes is sparse. Most studies on simulation report only anecdotal results rather than data obtained using evaluative tools. Objectives: The aim of this study was to examine student perception of best educational practices in simulation and to evaluate their satisfaction and self-confidence in simulation. Design: This study was a descriptive study designed to explore students' perceptions of the simulation experience over a two-year period. Using the Jeffries framework, a Simulation Day was designed consisting of serial patient simulations using high and medium fidelity simulators and live patient actors. Setting: The setting for the study was a regional campus of a large Midwestern Research 2 university. Participants: The convenience sample consisted of 199 participants and included sophomore, junior, and senior nursing students enrolled in the baccalaureate nursing program. Methods: The Simulation Days consisted of serial patient simulations using high and medium fidelity simulators and live patient actors. Participants rotated through four scenarios that corresponded to their level in the nursing program. Data was collected in two consecutive years. Participants completed both the Educational Practices Questionnaire (Student Version) and the Student Satisfaction and Self-Confidence in Learning Scale. Results: Results provide strong support for using serial simulation as a learning tool. Students were satisfied with the experience, felt confident in their performance, and felt the simulations were based on sound educational practices and were important for learning. Conclusions: Serial simulations and having students experience simulations more than once in consecutive years is a valuable method of clinical instruction. When conducted well, simulations can lead to increased student satisfaction and self-confidence. Highlights: The results of this study provide strong support for using a serial simulation as a learning tool. All aged students viewed the serial simulations as helpful to both learning and self-confidence. Simulation was a positive learning experience for the students who participated. Significant differences in overall satisfaction were seen in sophomore and senior students.